Musical Washing Machines, Composer-Performers, and Other Blurring Boundaries: How Women Make a Difference in Electroacoustic Music - Bosma, Hannah (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2006)
This essay explores the possibilities and limitations of an écriture féminine musicale in electroacoustic music. Theories by Cox, Dame, and Citron about "women's music" are discussed alongside research on women electroacoustic composers by McCartney and Hinkle-Turner, and analyses of works by Rudow, Isadora, and LaBerge. The operation of gendered musical categories is analysed in the appropriation of Cathy Berberian's "voice" by Berio. Strategies for destabilizing historically gendered categories in music are discussed, including feminine/feminist content, composer-performers, interdisciplinarity, and collaboration. The interdisciplinary character of many women's work may hamper its documentation and thus its survival. The author's research at NEAR/Donemus focuses on this problem.